Improved Aptamers for the Diagnosis and Potential Treatment of HER2-Positive Cancer - Marlies Gijs; Gregory Penner; Garth B. Blackler; Nathalie R.E.N. Impens; Sarah Baatout; André Luxen; An M. Aerts (MDPI AG, 2016)
Aptamers provide a potential source of alternative targeting molecules for existing antibody diagnostics and therapeutics. In this work, we selected novel DNA aptamers targeting the HER2 receptor by an adherent whole-cell SELEX approach. Individual aptamers were identified by next generation sequencing and bioinformatics analysis. Two aptamers, HeA2_1 and HeA2_3, were shown to bind the HER2 protein with affinities in the nanomolar range. In addition, both aptamers were able to bind with high specificity to HER2-overexpressing cells and HER2-positive tumor tissue samples. Furthermore, we demonstrated that aptamer HeA2_3 is being internalized into cancer cells and has an inhibitory effect on cancer cell growth and viability. In the end, we selected novel DNA aptamers with great potential for the diagnosis and possible treatment of HER2-positive cancer.